Optimized and parallelized implementation of the electronegativity equalization method and the atom-bond electronegativity equalization method - Svobodová Vařeková, Radka, 1977-; Masarykova univerzita. Katedra teoretické a fyzikální chemie (2006)
Nejčastěji používanými metodami pro výpočet náboje atomů v rámci molekuly jsou ab-initio kvantově mechanické metody. V nedávné době byly vyvinuty rychlejší metody pro výpočet náboje - eqalizační metody EEM (electronegativity equalization method) a ABEEM (atom-bond electronegativity equalization method), které jsou založeny na DFT (density functional theory). V této práci byly metody EEM a ABEEM implementovány a optimalizovány, přičemž byly vytvořeny programy EEM SOLVER a ABEEM SOLVER. Tyto programy byly otestovány a bylo ověřeno, že jejich výsledky dosahují požadované přesnosti a že jsou výrazně rychlejší než ab-initio metody. Bylo zjištěno, že nejvíce časově náročnou částí equalizačních metod je redukce matice soustavy rovnic, vygenerované při výpočtu. Z tohoto důvodu byla uvedená část algoritmu nahrazena paralelním algoritmem a implementována pomocí PVM (parallel virtual machine).
The most common way to calculate charge distribution in a molecule is ab-initio quantum mechanics. Some faster alternatives to quantum mechanics have also been developed, so called equalization methods EEM (electronegativity equalization method) and ABEEM (atom-bond electronegativity equalization method), which are based on density functional theory. In this work, the EEM and ABEEM methods were implemented and optimized and the EEM SOLVER and ABEEM SOLVER programs were developed. These programs were tested and it was verified that they have adequate accuracy and are markedly faster than ab-initio methods. It has been found that the most time-consuming part of equalization methods is the reduction of the matrix belonging to the equation system generated by the method. Therefore, for both methods this part was replaced by the parallel algorithm and implemented within the parallel virtual machine environment.
Rigorózní práce (RNDr.)--Masarykova univerzita, Přírodovědecká fakulta, 2006.
Keywords: atom-bond electronegativity equalization method; electronegativity equalization method; molekuly; molecules; rigorózní práce; doctoral dissertations